Que faisiez-vous en 1989? - Feraru, Marcela (France, 2009)
In 1989, a wind of freedom blows over Europe. The chains of communist doctrine fall heavily to the ground. Initiated by Hungarians and Poles, the popular movement spreads to Czechoslovakia and sweeps the concrete blocks of the Berlin Wall before covering the body of dictator Ceausescu. From the testimonies of actors of the democratic march and the unpublished archives of the French army collected in Berlin and in Central Europe, the film What did you do in 1989? we discover these revolutions from the inside.
Verzio Film Festival Submission
Keywords: Documentary films